Healthcare professionals and commercial milk formula recommendations in the urban Mexican context - Hernández-Cordero, Sonia; Vilar-Compte, Mireya; Tomori, Cecília; Lara-Mejía, Vania; Rovelo-Velázquez, Natalia; Hayes, Keily; Pérez-Escamilla, Rafael (Frontiers in Public Health, 2023)
Breastfeeding (BF) is considered an essential component of optimal care for child health and development. In the past two decades, global data have shown improvements in some, but not all, BF indicators. Despite these positive changes sales and per capita intake of commercial milk formula (CMF) have increased globally. The CMF industry invests millions of dollars in marketing, which targets families and healthcare professionals (HCP). In Mexico, more than half of the mothers (53%) who feed their infants with CMF chose their brand on the recommendation of HCP. Understanding the reasons behind the current recommendations for the use of CMF by HCP is important for the design of BF interventions. The primary objective of this study was to explore Mexican HCP’ beliefs, attitudes, perceptions, and practices about early infant feeding practices, and reasons for recommending CMF. The secondary objective was to explore pregnant women and mother's perceptions of the infant feeding recommendations they received from HCP, and of the factors that influenced their infant feeding decisions. The study was based on a secondary qualitative data analysis of a WHO/UNICEF multi-country study. We analyzed focus group discussions (FGDs) and in-depth interviews (IDIs) from Mexico. Data were collected through convenience sampling in Mexico City and Guadalajara. HCP (n=34) analysis was based on IDIs, and pregnant women or mothers of children 0-18 months (n=74) on FGDs and IDIs. Through a thematic analysis, we identified the socioecology of BF and triangulated HCP and women’s accounts. HCP, pregnant women, and mothers recognized that several factors might have influenced their infant feeding decisions including healthcare facilities’ policies and maternal work conditions. Although HCP believed that BF is the best way to feed newborns and young children, they routinely recommended CMF. On the other hand, pregnant women and mothers had a strong belief that BF is the best way to feed their babies. However, when women sought support from HCP, the latter often recommended switching to CMF. This study highlights the discordance between HCP perceptions and mothers’ experiences of HCP recommendations about infant feeding. Our findings support a national call for policy actions.